Space and time in the child's mind: metaphoric or ATOMic? - Bottini, Roberto; Casasanto, Daniel (Frontiers in Psychology, 2013)
Space and time are intimately linked in the human mind, but different theories make different predictions about the nature of this relationship. Metaphor Theory (MT) predicts an asymmetric relationship between space and time. By contrast, A Theory of Magnitude (ATOM) does not predict any cross-dimensional asymmetry, since according to ATOM spatial and temporal extents are represented by a common neural metric for analog magnitude. To date, experiments designed to contrast these theories support MT over ATOM, in adults and children. Yet, proponents of ATOM have questioned whether some of the observed cross-dimensional asymmetries could be task-related artifacts. Here we conducted a test of the asymmetric relationship between space and time in children’s minds, equating the perceptual availability of spatial and temporal information in the stimuli more stringently than in previous experiments in children. Results showed the space-time asymmetry predicted by MT. For the same stimuli (i.e., snails racing along parallel paths), spatial information influenced temporal judgments more than temporal information influenced spatial judgments. These results corroborate previous findings in Greek children and extend them to children who speak Dutch and Brazilian Portuguese. The space-time asymmetry in children’s judgments is not due to task-related differences in the perceptual availability of spatial and temporal information in the stimuli; rather, it appears to be a consequence of how spatial and temporal representations are associated in the child’s mind.